Oxytocin receptor is a promising therapeutic target of malignant mesothelioma. Issue 9 (4th July 2021) - Kodama, Yuta; Tanaka, Ichidai; Sato, Tatsuhiro; Hori, Kazumi; Gen, Soei; Morise, Masahiro; Matsubara, Daisuke; Sato, Mitsuo; Sekido, Yoshitaka; Hashimoto, Naozumi
Abstract: Malignant mesothelioma (MM) is one of the most aggressive tumors. We conducted bioinformatics analysis using Cancer Cell Line Encyclopedia (CCLE) datasets to identify new molecular markers in MM. Overexpression of oxytocin receptor ( OXTR ), which is a G‐protein–coupled receptor for the hormone and neurotransmitter oxytocin, mRNA was distinctively identified in MM cell lines. Therefore, we assessed the role of OXTR and its clinical relevance in MM. Kaplan‐Meier and Cox regression analyses were applied to assess the association between overall survival and OXTR mRNA expression using The Cancer Genome Atlas (TCGA) datasets. The function of OXTR and the efficacy of its antagonists were investigated in vitro and in vivo using MM cell lines. Consistent with the findings from CCLE datasets analysis, OXTR mRNA expression was highly increased in MM tissues compared with other cancer types in the TCGA datasets, and MM cases with high OXTR expression showed poor overall survival. Moreover, OXTR knockdown dramatically decreased MM cell proliferation in cells with high OXTR expression via tumor cell cycle disturbance, whereas oxytocin treatment significantly increased MM cell growth. OXTR antagonists, which have high selectivity for OXTR, inhibited the growth of MM cell lines with high OXTR expression, and oral administration of the OXTR antagonist, cligosiban, significantly suppressed MM tumor progression in a xenograft model. Our findings suggest that OXTR plays a crucial role in MM cell proliferation and is a promising therapeutic target that may broaden potential therapeutic options and could be a prognostic biomarker of MM. Abstract : We identified high oxytocin receptor ( OXTR ) expression in malignant mesothelioma (MM), which was associated with poor overall survival. OXTR knockdown and administration of OXTR antagonists in vitro and in vivo experiments showed significant suppression of MM cell proliferation. These results indicate that OXTR could be a promising therapeutic target and a prognostic biomarker, enabling a personalized approach to the treatment of MM.